2014
DOI: 10.4314/bcse.v28i1.11
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and <i>in vitro</i> antimicrobial evaluation of 5-amino-7-aryl-6-cyano-4<i>H</i>- pyrano[3,2,<i>b</i>]pyrrole derivatives catalyzed by reusable ZrOCl<sub>2</sub>•8H<sub>2</sub>O

Abstract: ABSTRACT. An efficient synthesis of a new series of 5-amino-7-aryl-6-cyano-4H-pyrano[3,2-b]pyrrole derivatives from the reaction of 3-hydroxypyrrole, malononitrile, and various aromatic aldehydes using ZrOCl2·8H2O, an environmentally friendly catalyst under a thermal solvent-free green procedure is described. This simple protocol offer advantages such as shorter reaction times, simple work-up and excellent yield. The catalyst ZrOCl2·8H2O can be reused. The reusability of the catalyst has been studied for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It is observed that with other catalysts and particularly under reflux conditions the reaction times are very much higher. Under reflux conditions, synthesis of 5-amino-7-aryl-6-cyano-4H-pyrano[3,2-b]pyrrole derivatives catalyzed by (MTSA) [18], ZrOCl 2 ·8H 2 O [22] have been reported shorter reaction times, the present method offers a comparatively very low cost and easily producible nano Zinc Oxide for effective results. (Table 3)…”
Section: B Comparative Catalytic Activity Of Nano Zno With Other Catmentioning
confidence: 81%
See 1 more Smart Citation
“…It is observed that with other catalysts and particularly under reflux conditions the reaction times are very much higher. Under reflux conditions, synthesis of 5-amino-7-aryl-6-cyano-4H-pyrano[3,2-b]pyrrole derivatives catalyzed by (MTSA) [18], ZrOCl 2 ·8H 2 O [22] have been reported shorter reaction times, the present method offers a comparatively very low cost and easily producible nano Zinc Oxide for effective results. (Table 3)…”
Section: B Comparative Catalytic Activity Of Nano Zno With Other Catmentioning
confidence: 81%
“…As a consequence of this requirement, phases that have a low stability in bulk materials can become very stable in nanostructures. In the recent years, Pyranopyrrole derivatives have been reported by using various catalysts, such as melamine trisulfonic acid (MTSA) [18], Fe(HSO 4 ) 3 [19], Zirconium(IV) dichloride [20], [pmim]HSO 4 -SiO 2 [21], ZrOCl 2 ·8H 2 O [22]. However, these methods suffer from drawbacks, such as low yields of products, tedious workup procedures, the requirement of longer reaction time and high temperature.…”
Section: Introductionmentioning
confidence: 99%